Self-heating Risks Associated with Agromining Processes - Agnès Janès; Rémi Demol; Baptiste Laubie; Marie-Odile Simonnot; Olivier Dufaud (Chemical Engineering Transactions)
The thermal stability of powders and pellets from agromining and miscanthus was assessed using basket tests and thermogravimetric analyses. Isothermal basket tests were carried out according to ISO/TS 20049-2 standard. In addition to the thermal stability of the biomass piles, the combustion gases were analysed by micro-gas chromatography. The influences of storage temperature, dimension and pellet/powder size were studied. The significant effect of oxygen accessibility and bed permeability was highlighted. Although pellets produced from agromining appear to be slightly more sensitive to self-ignition than miscanthus, the deviation is not significant enough to require the implementation of specific, additional preventive measures. The presence of nickel, due to agromining process, does not appear to be the cause of this sensitivity.